2019
DOI: 10.5539/jas.v11n7p14
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive Method for Estimating the Leaf Area of Pear cv. ‘Triunfo’

Abstract: The present study had as objective to determine mathematical equations to estimate the leaf area of pear cv. 'Triunfo' using linear dimensions of the leaves. For that, 300 healthy leaves of different sizes from each quadrant of plants from the small farm of Boa Vista located in the city of Montanha, at the northern side of the State of Espírito Santo, Brazil were used. The length (L) along the main vein was measured, along with the maximum width (W) of the leaf blade and observed leaf area (OLA), in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…According to Maldaner et al (18), equations fitted with only one dimension of the leaf surface are more effective, since these models reduce the number of measurements in the estimation of leaf area by 50%, compared to models fitted based on the combination of measurements, which for Oliveira et al (10) makes the work easier to be carried out in the field. However, according to Espindula et al ( 19) these models must be well calibrated so that there is no biased estimation by these equations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Maldaner et al (18), equations fitted with only one dimension of the leaf surface are more effective, since these models reduce the number of measurements in the estimation of leaf area by 50%, compared to models fitted based on the combination of measurements, which for Oliveira et al (10) makes the work easier to be carried out in the field. However, according to Espindula et al ( 19) these models must be well calibrated so that there is no biased estimation by these equations.…”
Section: Resultsmentioning
confidence: 99%
“…The use of regression models generated from allometric measurements of leaves to estimate their area is a useful methodology in morphogenic studies (5), and has already been reported for several species such as Helianthus annuus L. (6), Crambe abyssinica (7), Jatropha curcas (2), Passiflora mucronata (8), Litchi chinensis Sonn. (9) and Pyrus communis L. (10). However, studies involving eggplant and eggplant were not found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of the ME is that it allows for non-destructive estimation of leaf area through the simple measurement of leaf length and width in situ. The ME has been widely used to estimate the leaf areas of various plant species, including woody plants [26,27], herbaceous plants [26,28,29], lianas [26,30], monocots [26,31,32], Magnoliids [25,26], ferns [26], and important crop species such as maize [33], pear [34], and grapes [35,36]. However, to apply the ME to estimate leaf area, a species-specific proportionality constant, known as the Montgomery parameter, must be determined in advance.…”
Section: Introductionmentioning
confidence: 99%